Factors of change of orientation of ecological training in conditions of sustainable development of Ukraine (local, regional, global levels) - Gnilusha , N. V. (Pedagogy of Higher and Secondary Education, 2012)
Hnilusha N. V. Factors of change of orientation of ecological training in conditions of sustainable development of Ukraine (local, regional, global levels). The article presents a theoretical substantiation o methodological principles of development of problem of regionalization of ecological education as a factor of professional training of environmentalists which are the high-quality index of an idea of cooperation of society and nature on different levels in the conditions of steady development of Ukraine.